Attitudes towards learning English as a second language among form four students / Martina Philip Lanat - Philip Lanat, Martina (2011)
The study seeks to achieve two main aims namely, to determine the students' level of attitudes towards learning ESL and to explore the students' views on their attitudinal motives of learning ESL. The study involved Form Four students of SM Tarat, situated about 20 kilometres from Kuching, the capital city of Sarawak. To assess the students' attitudes, a questionnaire was adapted from Karahan's (2007) Inventory derived from Buschenhofen (1998) comprising 23 items representing 6 main domains: educational and social status of English, social and instrumental value of English, the use of English would detract from cultural identity, orientations towards English, the intrinsic value of English language and English-based culture, and discomfort about Malaysian speaking English. The questionnaire was distributed based on a survey research design, employing a convenience sampling technique to 60 Form 4 students. The questionnaires were returned and analysed using Statistical Package for Social Sciences (SPSS) Version 17.0 for descriptive statistics. The results indicate that the students' attitudes were generally positive with mean scores within 3.0 for most of the 23 items. The study therefore revealed that Malaysian students to some extent were positive in their attitudes towards learning ESL.